EFFICACY OF INFORMATION SYSTEMS IN MANAGING ARCHIVES IN INDONESIA'S MINISTRY OF RELIGION'S OFFICE - Muhammad Ilham; Dwhy Dinda Sari; Zulkhairi Zulkhairi (PIONIR: JURNAL PENDIDIKAN, 2021)
The exponential growth of data, which occurs every day, can wreak havoc on records management. The more data, the more important the data collection process. It is very important to have reliable records management so that the records management process can run well. Information technology is one solution that can be used. Archive management using information technology is a method that allows archives to be easily organized according to their purpose and search. Information technology-based archive applications are very useful in terms of archive administration and the process of sharing archives with other units. The purpose of this study is to see how effective the use of information technology is in managing archives at the Ministry of Religion Office of Lhokseumawe City. Qualitative descriptive technique was used in this study, with data collection through interviews or conversations, as well as literature study. The results of this study indicate that the use of information systems in archive management, as well as the use of technology in archive management at the Office of the Ministry of Religion of Lhokseumawe City, is very useful and effective. Network constraints and the lack of human resources at the Office of the Ministry of Religion of Lhokseumawe City are one of the obstacles to its management.